Sources of funding for denominational higher education institutions in Poland - Mirosław Sitarz (Journal of Modern Science)
Objectives The aim of the article will be to analyze the applicable normative acts in the field of financing religious universities in Poland. Therefore, first the origins of financing higher education institutions will be presented, and then the current legal regulations regarding the financing of both higher education institutions of the Catholic Church and other churches and religious associations will be presented.